Vocational and professional education and training in Switzerland : success factors and challenges for sustainable implementation abroad - Strahm, Rudolf H. [Verfasser]; Geiger, Bruno H. [Verfasser]; Oertle, Cornelia [Verfasser]; Swars, Erik [Verfasser] (hep Verl., 2016)
"Why Swiss dual track education system has an excellent reputation throughout the world? Why Switzerland has the lowest rate of youth unemployment? Why Swiss industry's economic performance has been outstanding? How is comprehensive portrayal of Swiss dual track education system compared to the European educational systems? What success factors we have to consider and why they play a pivotal role in its implementation abroad? Various examples, enumerated from all over the world show how to start sustainable implementation." (Publisher, BIBB-Doku)
Die Akademisierungsfalle
Keywords: S 1.3.1 Ausbildung im Dualen System; S 2.3 Berufsbildungspolitik; I 1.1 Systemberatung; I 2.2.1 Westeuropa; Berufsbildungssystem; Duales System; Berufsbildungspolitik; Bildungsexport; Bildungstransfer; Internationale Zusammenarbeit; Schweiz